2021
DOI: 10.14814/phy2.14763
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metabolic capacity in fast and slow skeletal muscle via oxidative stress and the energy‐sensing of AMPK/SIRT1 in malnutrition

Abstract: The effects of malnutrition on skeletal muscle result in not only the loss of muscle mass but also fatigue intolerance. It remains unknown whether the metabolic capacity is related to the fiber type composition of skeletal muscle under malnourished condition although malnutrition resulted in preferential atrophy in fast muscle. The purpose of the present study was to investigate the effects of metabolic capacity in fast and slow muscles via the energy‐sensing of AMPK and SIRT1 in malnutrition. Wistar rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…Our analysis showed a lower abundance of most of the mitochondrial proteins in response to UND, as highlighted by the reduced levels of several key enzymes in the Krebs cycle, β-oxidation, and OXPHOS complexes in both PL and SOL muscles. In line with this analysis, previous reports have shown altered mitochondrial function in the skeletal muscle of malnourished rats [17,18,52,55]. Our results indicate that alteration in mitochondrial function during UND is further complicated by the decrease in mitochondrial content.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis showed a lower abundance of most of the mitochondrial proteins in response to UND, as highlighted by the reduced levels of several key enzymes in the Krebs cycle, β-oxidation, and OXPHOS complexes in both PL and SOL muscles. In line with this analysis, previous reports have shown altered mitochondrial function in the skeletal muscle of malnourished rats [17,18,52,55]. Our results indicate that alteration in mitochondrial function during UND is further complicated by the decrease in mitochondrial content.…”
Section: Discussionsupporting
confidence: 91%
“…We found that UND had effects on the glycolytic PL muscle but had no significant effect on the oxidative SOL muscle. These findings are corroborated by previous data, demonstrating that UND does not affect muscle mass and protein synthesis in aged SOL muscle [17,25] and does not affect muscle mass and fiber CSA in adult SOL muscle [52]. Whether undernutrition affects the muscle fiber type composition remains undescribed.…”
Section: Discussionsupporting
confidence: 89%
“…Albumin plays an antioxidant role in blood vessels ( Taverna et al, 2013 ). ( Hirabayashi et al, 2021 ) reported that chronic malnutrition with hypoalbuminemia results in increased oxidative damage in skeletal muscle, and our results also confirm this. The present research explores, for the first time, the antioxidant effect of PF on skeletal muscle and TNF-α-treated C2C12 cells.…”
Section: Discussionsupporting
confidence: 90%
“…PGC-1α modulates mitochondrial dynamics and bioenergetics and increases mitochondrial mass and function, thereby enhancing the energy supply. The threonine 172 site and its phosphorylation play an essential role in the regulation of AMPK activity ( Hirabayashi et al, 2021 ). The AMPK signaling pathway mediates several beneficial functions, including ATP production, and maintains redox potential, which ensures optimal mitochondrial functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation